2016
DOI: 10.1039/c6ra14242g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of three-dimensional NiCo2O4 with different morphology for supercapacitors

Abstract: The morphology of NiCo2O4 can be controlled by changing the kinds of alkali source and the addition of NH4F, influencing its electrochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…Different types of synthesis methods for transition-metal-based oxides have been developed including hydroxide decomposition [19], nanocasting [20], electrodeposition [21], coprecipitation [22], and hydrothermal synthesis [23]. However, their complex and energy-consuming processing hinders the industrial application to glucose sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of synthesis methods for transition-metal-based oxides have been developed including hydroxide decomposition [19], nanocasting [20], electrodeposition [21], coprecipitation [22], and hydrothermal synthesis [23]. However, their complex and energy-consuming processing hinders the industrial application to glucose sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring fast, environmentally friendly, and energy-efficient synthetic methods for transition-metal-based oxides is urgent. Recently, it has been reported that chemical bath synthesis has proven to be capable of controlling the size and morphology of materials by control of reaction parameters, such as temperature, pH, and solvent concentration [ 23 , 24 , 25 , 26 ]. It is expected that the transition-metal-based oxides prepared by chemical bath synthesis can be applied as a glucose sensor.…”
Section: Introductionmentioning
confidence: 99%
“…These OH − ions then react with Ni +2 and Co +2 ions to form bimetallic hydroxide seed particles, as illustrated in the below equations. [ 64,65 ] These seed particles integrated themselves into the sheet‐like morphology as the methenamine surfactant encourages the radial growth, as shown in Figure 1c CH26normalN4 + 6normalH2O 6HCHO + 4NH3 NH3+normalH2O NH4+ +OH 2Co2+ +Ni2+ +2OH NiCo2OH2 …”
Section: Resultsmentioning
confidence: 99%
“…The P‐Ni x Co 9‐x S 8 sample shows the smallest diameter, suggesting a low charge transfer resistance of P‐Ni x Co 9‐x S 8 . Besides, the P‐Ni x Co 9‐x S 8 has the most vertical line in the low frequency range, indicating the ideal capacitor behavior and the lowest electrolyte diffusion impedance The EIS spectra are fitted based on the equivalent circuit model in the inset of Figure , The R s and R ct of the P‐Ni x Co 9‐x S 8 and Ni x Co 9‐x S 8 is 0.77 Ω ⋅ cm −2 , 0.78 Ω ⋅ cm −2 and 0.87 Ω ⋅ cm −2 , 1.12 Ω ⋅ cm −2 .…”
Section: Resultsmentioning
confidence: 99%